Spectrum Of Microbial Isolates From Blood Culture In Febrile Neutropenia - Hasan, Md Kamrul; Kabir, Amin Lutful; Aziz, Md Abdul; Masud, Adnan Hasan; Bakkar, Sk Md Abu; Ahmed, Munim; Rahman, M Hafizur; Rahmman, M Mahbubur (Journal of Chittagong Medical College Teachers' Association, 2013)
Infection remains an important cause of morbidity and mortality in neutropenic hosts after chemotherapy or due to bone marrow failure. In the face of worldwide changes in the incidence and spectrum of bacteraemia, we evaluated 47 febrile neutropenic patients in the haematology department of BSMMU during the period of October 2009 to October 2010. The overall rate of blood culture positivity was 17% (8/47) which is similar to most of the recent study in the western world, but the bacterial spectrum is different from that in developed world [1,2,3,4] JCMCTA 2013 ; 24 (1): 19-21